Gendered mobilities and immobilities: Women’s and men’s capacities for agricultural innovation in Kenya and Nigeria - Bergman Lodin, Johanna; Tegbaru, Amare; Bullock, Renee; Degrande, Ann; Wopong Nkengla, Lilian; Gaya, Hyeladi Ibrahim (Informa UK Limited, 2019)
This paper discusses how gendered mobilities and immobilities influence women’s and men’s capacities to innovate in agriculture. The authors analyze four case studies from Western Kenya and Southwestern Nigeria that draw on 28 focus group discussions and 32 individual interviews with a total of 225 rural and peri-urban women, men and youth. Findings show that women in both sites are less mobile than men due to norms that delimit the spaces where they can go, the purpose, length of time and time of day of their travels.